New ribotype Clostridioides difficile from ST11 group revealed higher pathogenic ability than RT078. Issue 1 (1st January 2021) - Gu, Wenpeng; Wang, Wenguang; Li, Wenge; Li, Na; Wang, Yuanyuan; Zhang, Wenzhu; Lu, Caixia; Tong, Pinfen; Han, Yuanyuan; Sun, Xiaomei; Lu, Jinxing; Wu, Yuan; et al.
ABSTRACT: Clostridioides difficile is the predominant antibiotic-associated enteropathogen associated with diarrhoea or pseudomembranous colitis in patients worldwide. Previously, we identified C. difficile RT078 isolates (CD21062) from elderly patients in China, including two new ribotype strains (CD10010 and CD12038) belonging to the ST11 group, and their genomic features were also investigated. This study compared sporulation, spore germination, toxin expression, flagellar characteristics, and adhesion among these strains in vitro and analysed their pathogenic ability in vivo using animal models. The results showed sporulation and spore germination did not significantly differ among the three C. difficile strains. CD10010 and CD12038 showed higher transcriptional levels of toxins until 48 h; thereafter, the transcriptional levels of toxins remained constant among RT078, CD10010, and CD12038. RT078 showed a loss of flagellum and its related genes, whereas CD12038 showed the highest motility in vitro. Both CD10010 and CD12038 initially showed flg phase OFF, and the flagellar switch reversed to phase ON after 48 h in swim agar. Flagellar proteins and toxins were both upregulated when flg phase OFF changed to flg phase ON status, enhancing their pathogenic ability. CD12038 showed the highest adhesion to Hep-2 cells. Histopathology and inflammation scores demonstrated that CD12038 caused the most severe tissue damage and infection in vivo. The new ribotype strains, particularly CD12038, exhibit higher pathogenic ability than the typical RT078 strain, both in vitro and in vivo. Therefore, more attention should be paid to this new C. difficile strain in epidemiological research; further studies are warranted.